Integrating early child development into an existing health and nutrition program: evidence from a cluster-randomized controlled trial - Hemlock, Caitlin; Galasso, Emanuela; Weber, Ann M.; Randriamiarisoa, Tsirery Christian; Col, Mathilde; Dieci, Maria; Ratsifandrihamanana, Lisy; Fernald, Lia C.H. (BMC public health, 2024)
In low-resource settings, introducing child health programs into community services may compete for caregiver time. We analyzed the impact of a new early childhood development (ECD) program in rural Madagascar on family attendance at other health services and of adding at-home play materials on program attendance. We randomized 75 communities where community health workers (CHWs) implement an existing child health and nutrition program (Projet d'Amélioration des Résultats Nutritionnels or PARN), the status quo. We offered two 6-month cycles of 12 ECD sessions to eligible caregiver-child dyads (6-30 months) in 25 sites [T]; we added take-home play materials in Cycle 2 to 25 sites [T+]. We used differences-in-differences with administrative data to analyze the effect of offering ECD sessions on monthly PARN attendance (T+/T vs. C) among age-eligible children and the impact of toy boxes/libraries on monthly ECD session attendance (T + vs. T). We used random intercept models to analyze characteristics associated with program registration. We analyzed data for 9,408 dyads; 30% and 32% registered for the program in Cycle 1 and 2 (respectively). On average, CHWs delivered 11.4 sessions (SD: 1.5). Children from wealthier households who already attended PARN sessions were more likely to register, and we found no effect of T or T + on PARN attendance. Adding play materials did not affect monthly ECD session attendance. Children from more populated sites were less likely to participate in both ECD and PARN sessions. Integrating new services for ECD into the health system was feasible and did not reduce dyad participation in existing services. Investment in health services in more populated areas is needed to provide coverage to all eligible children. Novel strategies should be explored to engage the most vulnerable children in new and existing health services. AEA Social Science Registry (AEARCTR-0004704) on November 15, 2019 (prospective registration) and ClinicalTrials.gov (NCT05129696) on November 22, 2021 (retrospective registration).